Recent Trends and Developments in the Global Workplace and their Impact on Employment Relations in Kenya - Olungo, Kennedy (Annals of Spiru Haret University. Economic Series, 2021)
Various perspectives exist amongst people about globalisation- a phenomenon that have impacted local economies in terms of trade, foreign direct investments, agriculture, technology transfer, dominant culture, as well as international standards. This study relied on a mixed methodology approach, which is a combination of quantitative and qualitative approaches. A total of 500 closed ended questionnaires were distributed to the employees of the sampled companies, out of which 483 were satisfactorily responded to, which amounts to 97% response rate. In addition, 10 key employment relations stakeholders were interviewed. The findings of the study revealed that there has been an increase in the rate outsourcing by many orgnaistions in Kenya, which has partly contributed to raising incidents of downsizing and retrenchment that have exacerbated the level of unemployed. Technological advancements have also been noted as a major contributor to retrenchment in Kenyan organisations. Although technology has accelerated performance, which has helped many organisations to reduce the operational costs, it has at the same time affected employees who have lost their livelihood as a result of the incursion of advanced technological innovations. Many organisations are currently engaging employees on casual or temporary work, which are sourced from labour brokers as a cost cutting mechanism. This state of affairs has affected the morale and psychological contract of many workers in Kenyan.